Measurement of Natural and Artificial Radioactivity in Infant Powdered Milk and Estimation of the Corresponding Annual Effective Dose - Uwatse, O.B.; Olatunji, M.A.; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Bradley, D.A.; Alkhorayef, M.; Alzimami, K. (Mary Ann Liebert, 2015)
Infant powdered milk (i.e., infant formula) is a rich and convenient source of nutrients, substituting for human breast milk in many countries. Moreover, it is the basic foodstuff for the infants because of its mineral and protein content, which is essential for growth and development. However, there are still limited data on radioactivity levels in infant powdered milk around the world, including Malaysia, for radiological health risk assessment. Thus, it is important to assess the radioactivity levels and the associated dose in the widely consumed powered infant milk. As a result, activity concentrations of 226Ra, 232Th, 40K, and 137Cs were determined in 14 brands of powdered milk consumed by Malaysian infants, which are imported from various regions around the world. Mean activities of 226Ra, 232Th, 40K, and 137Cs were 3.05±1.84, 2.55±2.48, 99.1±69.5, and 0.27±0.19Bq/kg, respectively. Among the analyzed milk samples, the brand from Philippines (Lactogen) showed low level of radioactivity, while a Singaporean brand (S26 SMA Gold) showed the highest. The artificial radionuclide, 137Cs, is virtually not detected in most of the brands investigated. Estimated mean annual effective doses due to consumption of powdered milk were 635.13 and 111.45μSv/year for infants ≤1 year and infants 1-2 years old, respectively. The obtained dose value is significantly higher (in case of infants ≤1 year old) and lower (in case of infants 1-2 years old) compared to the UNSCEAR reported value (290μSv/year) for the general population. In general, values are lower than the FAO/WHO and ICRP recommended limit of 1.0mSv/year for all ages.